Optimalisasi Manajemen Persediaan Obat dan Bahan Medis Habis Pakai di RSUD Sleman - Mahmudi, Mahmudi; Nurhidayat, Syarif; Najamuddin, Yunan (Jurnal Abdimas Madani dan Lestari (JAMALI), 2023)
Sleman Local Government Hospital (RSUD) as a Regional Public Service Agency (BLUD) has a function to provide health services to the community without prioritizing profit maximization. RSUD Sleman is required to be able to provide high quality health services at the prices that are affordable to the community. For this reason, RSUD Sleman must be able to optimize revenue and carry out cost efficiency. In terms of optimizing revenue, RSUD Sleman needs to make changes to the service charges, while in terms of cost efficiency, RSUD Sleman needs to improve management of drug supplies and consumable medical materials. Currently, drug supply management at RSUD Sleman still has several weaknesses. These weaknesses for example that drug procurement is based on the request of each doctor (doctor-centric), some inventory recording is still done manually, and there is no integrated management information system for drug supplies and consumable medical materials. Apart from that, there is limited capacity in the medicine warehouse. This community development program was carried out to help RSUD Sleman to improve the management of drug supplies and consumable medical materials by improving the management of medical supplies with a management-centric approach. The methods used in this service are focus group discussions (FGD), interviews, observation, and document analysis. The output of this program is a study of the management of drug supplies and consumable medical materials at RSUD Sleman which contains problem analysis and recommendations for improvement.